Combined laparoscopic and thoracoscopic repair of a large traumatic diaphragmatic hernia: a case report - Nor Hanipah, Zubaidah; Amir, Azuawarie; Ong, Kheng Wah; Gee, Tikfu (Malaysian Medical Association, 2015)
Traumatic diaphragmatic hernia is a well known complication of blunt trauma to the abdomen and thorax. In the acute setting, laparotomy is mandatory. In this current era, this condition can be managed with minimally invasive surgery. We hereby report a case of delayed large left diaphragmatic hernia that was repaired with a combination of laparoscopic and thoracoscopic approach.